Peranan Kepala Sekolah Dan Penerapan Nilai-Nilai Karakter Pada Gugus Lampeuneurut Aceh Besar - Fajri, Anisatul; Musdiani, Musdiani; Rahmatullah, Rahmatullah (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to know and analyze the role of school principals in the application of character values in the Aceh Besar Lampeuneurut cluster and to know the values of character education in the Aceh Besar Lampeuneurut cluster. The research was conducted using a qualitative approach. Data collection techniques used in this study consisted of in-depth interviews, observations, and documentation. Data analysis techniques use data condensation, data display, and conclution drawing to determine the role of the principal and the application of character values. The result of the study is the role of school principals in the Aceh Besar Lampeuneurut Cluster, acting as leaders, managers, supervisors, and motivators. In applying character values to the Aceh Besar Lampeuneurut Cluster by directing teachers to set good examples, provide guidance, direction, hold character development, extra-curricular, and religious activities. There are various obstacles for school principals in implementing character values in the Aceh Besar Lampeuneurut Cluster